Cocoa Theobroma, Trinidad. B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
A picture of cocoa pods on a branch. The pod contains the cacao beans that are fermented, roasted, and processed to extract cocoa powder and chocolate.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cacao--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Theobroma--Trinidad and Tobago